Potencial de isolados de Trichoderma e de leveduras no biocontrole da murcha-de-fusário do tomateiro - FONTES, Maria Geane (2013)
The fusarium wilt is a major disease in tomato and cause reduction in productivity and product quality. This study aimed to evaluate the efficiency of Trichoderma species and yeasts as agents biocontrollers of fusarium wilt in tomato caused by Fusarium oxysporum f. sp. lycopersici race 3. For this, tomato seedlings at 21 days were transplanted to pots containing soil infested with 50 g of substrate colonized with F. oxysporum f. sp. lycopersici and with Trichoderma (8g/vaso). In the experiment aiming at the selection of yeast inoculation was performed by the method of root pruning where tomato seedlings at 21 days were immersed in cell suspension (1.5 x107 cells/mL) of yeast and transplanted to pots, previously infested structures with the pathogen. We also assessed the effect of different dosages of inoculum of Trichoderma (2, 4, 6, 8 and 10g) and different concentrations of yeast (104, 105, 106, 107, 108 cells/mL). The antagonistic activity of Trichoderma in vitro was assessed by base pairing in culture. Antagonism of yeast was performed by means of continuous groove, the center of the Petri dish and two discs culture medium pathogen positioned 0.2 cm from opposite ends of the plate. Of the 48 isolates of Trichoderma tested four (T25, LCB72, LCB80 and LCB 48Te) were the most effective in reducing disease severity, and the isolate T25 promoted the highest level of disease control (71.2%). The values of the effective dose for 50% reduction in disease severity (ED50), the lowest values were presented by isolated LCB 48Te (6.8 g) and LCB80 (7.2 g), indicating that they are more effective in controlling of the disease. Of the 45 tested yeasts, four (Hanseniaspora opuntia, Pichia kluyveri, P. caribbica and P. fermentans) decreased by 100% severity of fusarium wilt. The values of the effective concentration for 50% reduction in disease severity (EC50), the lowest values were presented by isolated 28FR (2.1x106 cells/mL) and 32FR (2.3x106 cells/mL), indicating they are the most effective in controlling the disease. With regard to the production of the four yeast killer phenotype presented as positive. In in vitro tests, Trichoderma T25, LCB72, LCB80 and LCB 48Te completely inhibited the pathogen, and the isolated yeast 39F2B was the most effective in inhibiting the mycelial growth of the pathogen.